Community Intervention in Elderly Population: a Fall Prevention Project - Coimbra, Vera (2018)
The data collected was used for the production of epidemiological indicators, structure, process, and results. It is suggested to continue the project for one year, covering a larger sample and subsequent evaluation, and the creation of indicators for informal care providers.